2019
DOI: 10.1002/acr2.11049
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Thrombin Inhibition in Scleroderma‐Associated Interstitial Lung Disease

Abstract: ObjectiveInterstitial lung disease (ILD) is a frequent complication of systemic sclerosis (SSc) (scleroderma) and the leading cause of scleroderma‐related deaths. There exists an unmet need for a new drug therapy for ILD‐complicated SSc. Substantial evidence supports an important role for thrombin in the pathogenesis of SSc‐associated ILD (hereafter SSc‐ILD), and targeting thrombin with a direct thrombin inhibitor could prove to be a novel and effective treatment strategy. As a first step toward designing a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Second, alveolar hemorrhage may occur (and manifest as ILD) with apixaban and rivaroxaban, which, respectively, have higher metabolic liability (drug interaction potential) and bleeding risk as compared to dabigatran [1]. Conversely, the lack of consistent disproportionality for dabigatran is in agreement with current evidence and may have a biological rationale: marked anti-inflammatory and antifibrotic effects were demonstrated in a bleomycin model of ILD [7], and preliminary clinical evidence in 15 patients with ILD and systemic sclerosis showed good tolerability of dabigatran without serious adverse events [8].…”
Section: Dear Editorsupporting
confidence: 70%
“…Second, alveolar hemorrhage may occur (and manifest as ILD) with apixaban and rivaroxaban, which, respectively, have higher metabolic liability (drug interaction potential) and bleeding risk as compared to dabigatran [1]. Conversely, the lack of consistent disproportionality for dabigatran is in agreement with current evidence and may have a biological rationale: marked anti-inflammatory and antifibrotic effects were demonstrated in a bleomycin model of ILD [7], and preliminary clinical evidence in 15 patients with ILD and systemic sclerosis showed good tolerability of dabigatran without serious adverse events [8].…”
Section: Dear Editorsupporting
confidence: 70%
“…Moreover, thrombin was also demonstrated to stimulate fibroblast proliferation and myofibroblast transition [ 10 ]. Dabigatran has been studied in a 6-month, phase 1, prospective, single-centre, open-label study in SSc patients with interstitial lung disease (ILD) [ 11 ]. The dose was 75 mg twice daily.…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of dabigatran is not limited to the prevention of drug-induced ILD, as ILD is a frequent complication of fibrotic disease such as systemic sclerosis (SSc). A recent, prospective, open-label clinical study indicated that dabigatran appears to be safe and well tolerated in patients with SSc-associated ILD ( Silver et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%